Encyclopedia of Computational Mechanics 2004
DOI: 10.1002/0470091355.ecm030
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Plasticity and Evolution of Polycrystalline Microstructure

Abstract: The continuum slip theory of crystals provides a canonical framework of finite plasticity with physically well‐defined roots in the dislocation mechanics of metals. Reliable algorithmic settings of crystal plasticity are not only needed for structural analyses of single crystals but also provide a cornerstone for multiscale computations of evolving anisotropic microstructures in metallic polycrystals. This article summarizes a current status of computational crystal plasticity and its application to the textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The single crystal plasticity theory, discussed in detail by Asaro (1983) and Miehe and Schotte (2004), is used in this work. The deformation gradient F is assumed to decompose multiplicatively, as,…”
Section: Constitutive Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The single crystal plasticity theory, discussed in detail by Asaro (1983) and Miehe and Schotte (2004), is used in this work. The deformation gradient F is assumed to decompose multiplicatively, as,…”
Section: Constitutive Modelmentioning
confidence: 99%
“…The plastic deformation map F p defines the cumulative effect of dislocation motion. The evolution equation for the plastic deformation map is written as (Miehe and Schotte, 2004)…”
Section: Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we compare the new purely geometric formulation of rigid crystal plasticity with results obtained by elasto-plastic crystals formulations with active set search outlined in Miehe et al (2002) and Miehe and Schotte (2004) and by results obtained for the standard power-type setting of rigid crystal plasticity. It is shown that the new geometric approach yields very accurate estimates for the reorientation of single crystals and provides an extremely attractive fast estimate for texture developments in polycrystals.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…We refer to the standard setting of crystal plasticity with power laws by Peirce et al (1982) and the advanced computational settings based on active set definitions by Cuitin˜o and Ortiz (1992), Anand and Kothari (1996), Miehe et al (2002), and Ortiz and Stainier (1999). The recent review article Miehe and Schotte (2004) provides an overview. Micro-macro linking hypotheses drawn for the general theoretical framework of homogenization are outlined in Miehe et al (1999) and Miehe et al (2002).…”
Section: Introductionmentioning
confidence: 99%